Effect of tool surface topography on friction with carbon fibre tows for composite fabric forming. (February 2017) - Mulvihill, Daniel M.; Sutcliffe, Michael P.F.
Abstract: The effect of tool surface roughness topography on tow-on-tool friction relevant to the dry forming of composite fabrics is investigated. A comprehensive range of tool average surface roughness Ra values from 0.005 to 3.2 μm was used in friction testing with carbon fibre tows. The measured slope of these surfaces, which is the critical surface topographical characteristic, increased significantly with increasing roughness amplitude. Friction was found to be sensitive to roughness topography for very smooth surfaces ( Ra < 0.1 μm) and increased with decreasing roughness slope and amplitude. For rougher surfaces ( Ra > 0.1 μm), friction was relatively insensitive to roughness slope and amplitude. A finite element idealisation of the tow-on-tool contact was used to explain these results in terms of the level of tow-tool conformance. Smooth surfaces have low slopes which allow good conformance, and hence high real contact area and friction. Rougher surfaces have high slopes, particularly at shorter wavelengths, which prevents good conformance. In this case, point contact between fibres and surface dominates, leaving the resulting friction less sensitive to roughness.